Anatomic Variations of Brachial Plexus: A Cadaveric Study - Mohammad Sadegh Gholami Farashahi; Amir Hossein Mohammadi; Farid Abolhasani (Negah Institute for Scientific Communication, 2014)
Introduction: The brachial plexus is responsible for the innervation to the upper limb and some parts of the thorax. Variations in the branching of the brachial plexus are common and have been reported in 65.3% of the population. The variations (Atypical communication) of brachial plexus have significant clinical and surgical importance. Methods: In this study 10 upper limbs which belonged to 5 adult human cadavers of known sex are used. Results: In the present study, three cases (in two cadavers) of 10 cases (in five cadavers) have connections between the musculocutaneous and median nerve and seven cases are normal. Conclusion: Knowledge about the connections between the musculocutaneous nerve and the median nerve could be very useful in surgical operations on the humerus bone and shoulder joint. So, the more information we could collect about these structures and their variations, the safer the surgical operations could be done.